2022
DOI: 10.1155/2022/1937431
|View full text |Cite
|
Sign up to set email alerts
|

Thinner Central Corneal Thickness is Associated with a Decreased Parapapillary Vessel Density in Normal Tension Glaucoma

Abstract: This retrospective cross-sectional study, which enrolled 124 normal tension glaucoma (NTG) eyes and 68 healthy eyes as the control, determined the association between central corneal thickness (CCT) and ocular parameters in NTG. CCT was measured using the Pentacam® system, optical coherence tomography angiography (OCT-A) was adopted to measure the peripapillary and macular area VDs, and spatial data were based on the Garway–Heath map as illustrated in OCT-A. Univariate and multivariate linear regressions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our findings of lower optic disc perfusion in glaucomatous eyes compared with age-, AL-, and OPP-matched healthy eyes were consistent with the findings from previous studies that showed decreased microvascular density in the optic disc of glaucoma patients [38][39][40][41]. Patients with POAG and LTG have lower perfused capillary density and optic disc perfusion compared with healthy controls [10,12]. Therefore, OCT-A can dif- LTG is less dependent on the IOP and may have a greater component of abnormal vascular function compared with HTG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of lower optic disc perfusion in glaucomatous eyes compared with age-, AL-, and OPP-matched healthy eyes were consistent with the findings from previous studies that showed decreased microvascular density in the optic disc of glaucoma patients [38][39][40][41]. Patients with POAG and LTG have lower perfused capillary density and optic disc perfusion compared with healthy controls [10,12]. Therefore, OCT-A can dif- LTG is less dependent on the IOP and may have a greater component of abnormal vascular function compared with HTG.…”
Section: Discussionsupporting
confidence: 91%
“…Xu et al [42] found that the peripapillary vascular density was significantly lower in LTG patients than HTG patients. There is no difference in the optic disc perfusion between patients with POAG and LTG who have similar levels of VF damage [12, 43]. POAG patients have lower perfused capillary density compared with LTG patients [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thinner corneas correlated with the response of the corneoscleral shell and the ocular vasculature to IOP-induced stress [47]. A recent study demonstrated thinner CCT is associated with a decreased parapapillary vessel density in NTG [48].…”
Section: Discussionmentioning
confidence: 92%
“…The chaung study found significant thinner cornea in normal-tension glaucoma. They found also, that reduced corneal thickness in NTG correlated with decreased RPC peripapillary vessel density [ 33 – 35 ].…”
Section: Discussionmentioning
confidence: 99%